Comparison of virulence between Paracoccidioides brasiliensis and Paracoccidioides lutzii using Galleria mellonella as a host model - Scorzoni, Liliana [UNESP]; De Paula e Silva, Ana Carolina Alves [UNESP]; De Lacorte Singulani, Junya [UNESP]; Leite, Fernanda Sangalli [UNESP]; De Oliveira, Haroldo Cesar [UNESP]; Da Silva, Rosangela Aparecida Moraes [UNESP]; Fusco-Almeida, Ana Marisa [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (Taylor & Francis, 2015)
Paracoccidioidomycosis is a systemic mycosis, endemic in Latin America. The etiologic agents of this mycosis are composed of 2 species: Paracoccidioides brasiliensis and P. lutzii. Murine animal models are the gold standard for in vivo studies; however, ethical, economical and logistical considerations limit their use. Galleria mellonella is a suitable model for in vivo studies of fungal infections. In this study, we compared the virulence of P. brasiliensis and P. lutzii in G. mellonella model. The deaths of larvae infected with P. brasiliensis or P. lutzii were similar, and both species were able to reduce the number of hemocytes, which were estimated by microscopy and flow cytometer. Additionally, the phagocytosis percentage was similar for both species, but when we analyze hemocyte-Paracoccidioides spp. interaction using flow cytometer, P. lutzii showed higher interactions with hemocytes. The gene expression of gp43 as well as this protein was higher for P. lutzii, and this expression may contribute to a greater adherence to hemocytes. These results helped us evaluate the behavior of Paracoccidioides spp in G. mellonella, which is a convenient model for investigating the host-Paracoccidioides spp. interaction. © 2015 Taylor & Francis Group, LLC.
Keywords: Adhesin; Adhesion; Galleria mellonella; gp43; Hemocyte; Paracoccidioides spp; Virulence